TRAVEL BEHAVIOUR AMONG THE DISABLED TOURISTS IN KUALA LUMPUR - MUSA, GHAZALI (ASEAN Journal on Hospitality and Tourism, 2008)
This paper is an exploratory study with the aim to examine travel motivation, travel difficulty and destination preference among the disabled community in Kuala Lumpur. A questionnaire was derived from focus group discussions, in-depth interviews and literature review. The questionnaires were distributed using convenience sampling and 176 of them returned and analyzed. The majority of respondents are young, pre-dominantly male and unemployed. They do take holidays especially to domestic destinations and most times accompanied by friends and family members. Disabled people face considerable difficulty especially in terms of accessibility and finance. The main travel motivations are to see new places and to relax, and the most preferred destination is nature. The result reveals significant relationships between the components of destination preference with the components of travel motivation and travel difficulty. It is proposed that both government and society should intensify the present effort to raise the living standard of disabled people, to improve general accessibility, and to increase public awareness of disabled people’s equal status in the society. The disabled themselves also should be out there in the public scene to further justify their needs of accessible facilities and infrastructure.